Invisibility cloak designed with AI - Yang, Tong (Nanyang Technological University, 2022)
Stealth technology has developed very rapidly in the past few years, but still faces serious bottlenecks, such as bandwidth, superluminal speed limit, dispersion, loss and so on. In this dissertation, a stealth model which implanted epical stealth methods that can combine all the technical metrics of all current major stealth strategies to solve the bottlenecks of individual strategies has been designed and investigated.. A broadband cylindrical stealth in free space is designed based on scattering cancellation (the previous method for plasmatic stealth), together to validate practical fabrication possibility using anisotropic metamaterials (a unique feature of previous transforming optical stealth). In this dissertation the tradition method has been combined with trend leading technology Genetic Algorithm optimization method to help better confine the constitutive parameter, proving that the machine learning algorithm do contributes to excellent performance in all evaluating metrics. On the basis of the GA (Genetic Algorithm) optimization algorithm, the relationship between the inner boundary and the outer boundary and the wavelength, the number of layers of the cloak design, and other parameters on the cloak's stealth effect are also proved in this dissertation